MiRNATissueAtlas2: an update to the human miRNA tissue atlas. Issue Volume 50:Issue D1(2022) (27th September 2021) - Keller, Andreas; Gröger, Laura; Tschernig, Thomas; Solomon, Jeffrey; Laham, Omar; Schaum, Nicholas; Wagner, Viktoria; Kern, Fabian; Schmartz, Georges Pierre; Li, Yongping; Borcherding, Adam; Meier, Carola; et al.
Abstract: Small non-coding RNAs (sncRNAs) are pervasive regulators of physiological and pathological processes. We previously developed the human miRNA Tissue Atlas, detailing the expression of miRNAs across organs in the human body. Here, we present an updated resource containing sequencing data of 188 tissue samples comprising 21 organ types retrieved from six humans. Sampling the organs from the same bodies minimizes intra-individual variability and facilitates the making of a precise high-resolution body map of the non-coding transcriptome. The data allow shedding light on the organ- and organ system-specificity of piwi-interacting RNAs (piRNAs), transfer RNAs (tRNAs), microRNAs (miRNAs) and other non-coding RNAs. As use case of our resource, we describe the identification of highly specific ncRNAs in different organs. The update also contains 58 samples from six tissues of the Tabula Muris collection, allowing to check if the tissue specificity is evolutionary conserved between Homo sapiens and Mus musculus . The updated resource of 87 252 non-coding RNAs from nine non-coding RNA classes for all organs and organ systems is available online without any restrictions (https://www.ccb.uni-saarland.de/tissueatlas2 ).